A evoluç\~ao da segregaç\~ao por qualificaç\~ao profissional ao nível das firmas - Luiz Dias Bahia; Danilo Coelho; Alexandre Messa Silva; Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This article measures the evolution of segregation by skill level among firms in the Brazilian formal labor market from 1996 to 2005. We define segregation as firms having a labor force composition by skill different from the labor market as a whole. We measure segregation using four different indicators for skill level: educational attainment, wages, job tenure, and age. Our main result is that, in contrasts to what has been observed in the United States, the United Kingdom and France, there is a reduction of educational segregation. This is a widespread phenomenon that can be observed in all five of Brazil`s regions.
Keywords: J21; J24; 330